2005
DOI: 10.1302/0301-620x.87b10.16160
|View full text |Cite
|
Sign up to set email alerts
|

Motility and growth of human bone-marrow mesenchymal stem cells during ex vivo expansion in autologous serum

Abstract: Human bone-marrow mesenchymal stem cells have an important role in the repair of musculoskeletal tissues by migrating from the bone marrow into the injured site and undergoing differentiation. We investigated the use of autologous human serum as a substitute for fetal bovine serum in the ex vivo expansion medium to avoid the transmission of dangerous transfectants during clinical reconstruction procedures. Autologous human serum was as effective in stimulating growth of bone-marrow stem cells as fetal bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 21 publications
2
53
1
Order By: Relevance
“…Platelet factors such as platelet-derived growth factor, transforming growth factor, and epidermal growth factor that promote increased migration and proliferation of MSCs have been studied extensively [18 -20]. The effectiveness of human serum is based mainly on studies using autologous serum [16,21], whereas the reports on allogeneic serum have been contradictory [22,23]. Our aim was to compare the effectiveness of human serum and platelet factors in promoting MSC growth with FCS.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet factors such as platelet-derived growth factor, transforming growth factor, and epidermal growth factor that promote increased migration and proliferation of MSCs have been studied extensively [18 -20]. The effectiveness of human serum is based mainly on studies using autologous serum [16,21], whereas the reports on allogeneic serum have been contradictory [22,23]. Our aim was to compare the effectiveness of human serum and platelet factors in promoting MSC growth with FCS.…”
Section: Introductionmentioning
confidence: 99%
“…FBS also contains non-human antigens, such as N-glycolylneuraminic acid, which is an obstacle for its application in clinical cell therapy [15]. Human Serum (HS) has been introduced as an alternative for FBS that provide the required proteins stem cells with no risk of disease transmission and rejection [8,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that autologous serum has a positive influence on MSC behavior. 30 For positively charged molecules in particular, it is possible to stick to the negatively charged surface by SiO groups of the bone substitute and therefore promote the remodeling process. 31 Fibrin could cover the bone substitute surface and therefore mask the SiO groups, so that the matrix change and induction of bone formation could not take place.…”
mentioning
confidence: 99%